2020
DOI: 10.3390/urbansci4010007
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Memories for Better Place Experience: The Case of Orabi Square in Alexandria, Egypt

Abstract: Globalization is associated with significant transformations in city forms and cultural and social performances. Governments and cultural heritage organisations increasingly appreciate the importance of preserving diverse physical cultural heritage through rehabilitation and the implementation of conservation plans. Nevertheless, there is a need to evaluate whether these plans understand the importance of cultural memory in societies, as well as how it affects the human psyche. Utilizing Orabi Square, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Within our previous research, the case of Orabi Square, was utilized to contrast the site's historical versus current conditions in concert with the concept of place experience. This study demonstrated that cultural memory has an active role in shaping the emotional attachment to place, and contributes to a sense of place that promotes a rich quality of life and place experience [40]. Our recent publication on the demolished theatre 'Masrah Al Salam', presented a rich case to explore the importance given to cultural memory by the people inhabiting the study area.…”
Section: Cultural Memorymentioning
confidence: 77%
“…Within our previous research, the case of Orabi Square, was utilized to contrast the site's historical versus current conditions in concert with the concept of place experience. This study demonstrated that cultural memory has an active role in shaping the emotional attachment to place, and contributes to a sense of place that promotes a rich quality of life and place experience [40]. Our recent publication on the demolished theatre 'Masrah Al Salam', presented a rich case to explore the importance given to cultural memory by the people inhabiting the study area.…”
Section: Cultural Memorymentioning
confidence: 77%
“…The first paper addressed Orabi Square and the research focused on two particular aspects: changes in the fabric of the site over time, and place experience. In this case study, it was demonstrated that cultural memory actively promotes emotional attachment to place, which is important in the development of a sense of place, which in turn enables higher QoL and an enhanced place experience (Hussein et al 2020b). The second paper addressed our research into Masrah Al Salam.…”
Section: Formulating Conclusion/construction Of Theory (Third Phase)mentioning
confidence: 81%
“…To do this, the paper refers to case studies previously conducted at three sites in Alexandria, Egypt, in the Orabi Square, Masrah Al Salam context and Zanqit Alsitat market. Each of these places have been the subject of published research papers (Hussein et al 2020a(Hussein et al , 2020b(Hussein et al , 2020c that have developed GT to advantage in analysis. This paper uses these case studies as a ground for the discussion of GT as an approach for exploring the effect of cultural memory on psychosocial well-being in historic urban landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, we utilised the case of Orabi Square, as one of the HULs in Alexandria (Egypt), in order to explore the site's historical and new conditions and place experience. In the aforementioned study, we were able to demonstrate that cultural memory is an active catalyst for emotional attachment to place, and is an important factor informing sense of place for better place experience [44].…”
Section: Introductionmentioning
confidence: 78%
“…The interview questions were designed, and pilot tested on two interviewees to check questions for clarity and to identify the time requirements. The pilot interviews resulted in minor modifications to the wording of the questions, and the final revised semi-structured interview consisted of 20 questions covering the research's conceptual themes [44].…”
Section: Data Collection and Analysismentioning
confidence: 99%